‘Amadodana enu abone imibono’: The interpretation of Ntsikana’s vision against the book of Acts’s vision experiences - Jentile, Thembelani E. (Verbum et ecclesia, 2024)
The specific aim of this article is to interpret Ntsikana’s kraal vision by considering the vision narratives or experiences found in Acts of the Apostles. In 1987, J.B. Peires interpreted this vision as a mere ‘hallucination’ and further argued that there was nothing Christian about it, stating that Ntsikana had experienced a mystical vision, like any other heathen diviner. This article partly differs from this interpretation, and an argument is pursued that in South African church history vision narratives have led to ‘conversion(s)’ of many church leaders, including Ntsikana, and have subsequently shaped the direction of the church, especially the African indigenous churches. It is noted that the writer of Acts employed visions more frequently than any other author in the New Testament and that at strategic places throughout his work, Luke reported epiphanies in which God, or a divine agent, appeared and guided the course of events. These experiences, as reported by Luke, are not far from what Ntsikana experienced and should therefore be read as constituting the act of God in an African context.Intradisciplinary and/or interdisciplinary implicationsThe study has significance for Church history, African traditional religion and the New Testament. It is undertaken within (intra-) the African traditional and Christian religions discourse, with an interest in Church History that combines philosophical and theological approaches, especially with reference to South African sociopolitical and ecclesiastical contexts. The research builds on the existing Church history and New Testament discourses.